Research note: Protective effects of compound mycotoxin detoxifier in broiler chicken fed aflatoxins-contaminated diets - Kourosh Gholami Ahmadabadi; Mahsa Rahimi; Hamid Raei; Reza Majedifar; Mohammad Amir Karimi Torshizi (Poultry Science)
This study was planned and executed to investigate the effects of two levels of compound toxin binder (CTB) on growth performance, serum biochemistry, antioxidant status, intestinal morphology, and the ileal selected microflora population in broiler chickens. A total of 240 one-day-old Ross 308 broiler chickens were divided into four treatments and six replicates (10 chickens per replicate). Experimental groups included; 1, negative control (NC; no aflatoxins (AFs) and no additives); 2, positive control (PC; 490 µg/kg AFs); 3, low levels of compound toxin binder (LCTB), PC + 1 g/kg available CTB (Navacidox); and 4, high levels of compound toxin binder (HCTB), PC + 2 g/kg Navacidox. Increasing body weight gain (BWG) following feeding HCTB were found compared to the PC (P < 0.05). The highest feed intake (FI) was observed in the NC (P < 0.05). Feeding broilers with AFs decreased villus height, villus width, and crypt depth compared to the NC (P < 0.05). The increasing lactic acid bacteria population in HCTB was recorded compared to the PC (P < 0.05). Among biochemistry parameters, total protein, LDL, and uric acid decreased in LCTB compared to the PC (P < 0.05). Lower concentrations of ALP, LDH, AST, and ALT in LCTB were observed compared to the PC (P < 0.05). Although total antioxidant capacity, GPx, and SOD activities were not affected by treatments (P > 0.05), the lowest catalase levels were found in HCTB (P < 0.05). In conclusion, AFs feeding impaired growth performance, biochemistry parameters, antioxidant capacity, and intestinal morphology. However, the inclusion of CTB in AFs-contaminated diets effectively mitigated the harmful effects of AFs.